PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PERUSAHAAN PT. KRAKATAU STEEL (PERSERO), TBK - Tauziah Hasinah; Nurul Huda (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to analyze the effect of Current Ratio, Total Asset Turnover on Return On Asset simultaneously and partially. Associative research type. Popolation used is financial report data (Balance Sheet and Profit and Loss Statement) for the year 2010-2019 PT. Krakatau Steel (Persero), TBK which is listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling by obtaining samples for the last ten years, namely the years 2010-2019, the data analysis technique used was multiple linear regression. The results showed that the Current Ratio partially did not have a significant effect on Return On Assets at PT. Krakatau Steel (Persero) Tbk and Total Asset Turnover partially do not have a significant effect on Return On Asset at PT. Krakatau Steel (Persero) Tbk while the Current Ratio (CR) and Total Asset Turnover (TATO) simultaneously are not significant and have no effect on Return On Asset (ROA). Keywords: Current Ratio, Total Asset Turnover, Return On Asset